Effect of different manipulations of the cluster-set method on training volume and time under tension in resistance training men - Ricardo Reis Dinardi; Frank Douglas Tourino; Lucas Túlio de Lacerda; João Batista Ferreira-Júnior; Hugo César Martins-Costa (Hospital de Clínicas de Itajubá, 2022)
Objective: To compare the acute effect of two training protocols until concentric failure (CF) with different intra-set interval (ISI) configurations (20 s and 40 s) on total weight, the total number of repetitions, and time under tension in trained subjects. Methods: Ten men participated in the study (age = 25.1 ± 4.4 years; body mass = 76.5 ± 10.4 kg; height = 175.8 ± 9.3 cm). Two protocols were performed with 4 sets of bench press exercises and differentiated by the ISI: i) Protocol ISI-40 (40 s) - each set consisted of 6 repetitions followed by an ISI of 40 s and completed with repetitions up to CF; ii) Protocol ISI-20 (20 s) - each set consisted of 6 repetitions with ISI of 20 s every 3 repetitions followed by repetitions to CF. The intensity was 10 repetitions maximum, and the rest interval between sets of 80 s. A minimum interval of 48 h was adopted between protocols. Results: There was no significant difference in the number of repetitions (p = 0.074), in the time under tension (p = 0.353) and in the total volume (p = 0.083) between the protocols. Conclusion: The results indicate that the different ISI configurations did not distinctly influence the number of repetitions, time under tension, and total volume.